Pengaruh Hambatan Samping Terhadap Kinerja Lalu Lintas Jalan Antang Raya Depan Pasar Antang - Maxi Lipu Bongga; Mary Selintung; Sufiati Bestari (Paulus Civil Engineering Journal, 2023)
The purpose of this study was to determine the degree of saturation, the average speed of light vehicles at peak hours, and the actual average speed of light vehicles at peak hours on Antang Raya road in front of Antang market. The method used refers to the Indonesian Road Capacity Guidelines (PKJI 2014). Data collection for 3 days at the research location by videoing traffic volume data, measuring the travel time of light vehicles traveling a distance of 50 m, and counting side friction events. The results of the analysis obtained a degree of saturation of 0.91> 0.85 meaning that the traffic flow on the Antang Raya road in front of Antang Market is jammed. Reading the 2014 PKJI graph shows that the average speed of light vehicles is 27 km/hour, and the calculation of the actual average speed of light vehicles is 8.64 km/hour. The speed of the reading of the graph and the calculation result is very different because the distance traveled by the light vehicles surveyed is 50 m which does not represent the speed of space. For the smooth flow of traffic on Antang Raya road in front of Antang market, it is recommended to install a no parking sign for 200 meters, during peak hours, police officers discipline drivers who are not disciplined, and street vendors selling on the shoulder of the road are neatly arranged so that buyers do not obstruct traffic flow.